Notch and wingless modulate the response of cells to hedgehog signalling in the Drosophila wing. - Glise, B.; Jones, D.L.; Ingham, P.W. (Developmental Biology, 2002)
During Drosophila wing development, Hedgehog (Hh) signalling is required to pattern the imaginal disc epithelium along the anterior-posterior (AP) axis. The Notch (N) and Wingless (Wg) signalling pathways organise the dorsal-ventral (DV) axis, including patterning along the presumptive wing margin. Here, we describe a functional hierarchy of these signalling pathways that highlights the importance of competing influences of Hh, N, and Wg in establishing gene expression domains. Investigation of the modulation of Hh target gene expression along the DV axis of the wing disc revealed that collier/knot (col/kn), patched (ptc), and decapentaplegic (dpp) are repressed at the DV boundary by N signalling. Attenuation of Hh signalling activity caused by loss of fused function results in a striking down-regulation of col, ptc, and engrailed (en) symmetrically about the DV boundary. We show that this down-regulation depends on activity of the canonical Wg signalling pathway. We propose that modulation of the response of cells to Hh along the future proximodistal (PD) axis is necessary for generation of the correctly patterned three-dimensional adult wing. Our findings suggest a paradigm of repression of the Hh response by N and/or Wnt signalling that may be applicable to signal integration in vertebrate appendages.